Pengaruh Beban Kerja dan Stres Kerja dengan Efikasi Diri pada Karyawan PT Mitra Intimarga Bekasi - Tungga Buana Irfana; Resti Wulan Purnama; Tungga Buana Diana (STIKes Ibnu Sina Ajibarang, 2024)
Human resource management is very important for companies in managing, organizing and utilizing employees so that they can function productively to achieve company goals. Labor or employees are very important human resources in a company, because without employees the company cannot run well. Employees are the main capital for the company. As, employee capital needs to be managed to remain productive. Therefore, company leaders must be able to encourage them to remain productive in carrying out their respective duties, by continuously increasing the morale of their employees. So that the company can maintain employee loyalty in order to achieve company goals.